Time and Cost of Diagnosis for Symptomatic Femoroacetabular Impingement. Issue 3 (7th March 2014) - Kahlenberg, Cynthia A.; Han, Brian; Patel, Ronak M.; Deshmane, Prashant P.; Terry, Michael A.
Background: Femoroacetabular impingement (FAI) and labral tears are common causes of hip pain that are often not promptly or properly diagnosed. To our knowledge, no reports have defined the time and cost of diagnosis of labral tears associated with FAI. Hypothesis: Patients with labral tears associated with FAI undergo extraneous diagnostic testing and pain and incur a significant amount of health care costs before they receive appropriate surgical management for their pathology. Study Design: Economic and decision analysis; Level of evidence, 4. Methods: A total of 78 patients diagnosed with symptomatic FAI were surveyed. A standardized questionnaire asked patients about time to diagnosis, symptoms, health care providers visited, imaging tests, and treatments prior to diagnosis. Costs were calculated based on 2012 national Medicare data. Results: Patients in the cohort saw an average of 4.0 health care providers, had an average of 3.4 diagnostic imaging tests, and tried an average of 3.1 treatments prior to diagnosis. The average total amount spent per patient prior to diagnosis was US2456.97. The calculated minimum cost of diagnosis, including a visit to an orthopaedic surgeon as well as an anteroposterior pelvis and lateral hip radiograph and 1 magnetic resonance arthrogram, was US690.62. The average duration between onset of symptoms and diagnosis of labral tear was 32.0 months. Conclusion: The average amount of health care dollars spent per patient prior to receiving a diagnosis of acetabular labral tear was US1766.35 higher than the calculated minimum cost. This figure is based on Medicare payment amounts, which may significantly underestimate the actual charges at many hospitals, thereby increasing the total cost of diagnosis. Clinical Relevance: The costs and pain associated with this time, along with the potential long-term degradation of the hip joint, make it important for all health care professionals to recognize and appropriately manage or refer the patient.